PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA CANVA DI KELAS IV SDN 21 BANDAR BUAT KOTA PADANG - Cornelia, Pira; Waldi, Atri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the improvement in Pancasila education learning outcomes using the Problem Based Learning (PBL) model assisted by Canva media in class IV at SDN 21 Bandar Buat, Padang City. This research applies a type of Classroom Action Research (PTK) using qualitative and quantitative approaches. The subjects in this research were teachers (researchers) and 16 students consisting of 10 men and 6 women. The results of this research show an increase in: a) the first cycle Teaching Module obtained an average of 89.58% (B), and in the second cycle 95.83% (SB). b) The results of the implementation in the teacher aspect of cycle I obtained an average of 85.71% (B), and cycle II 96.42% (SB). c)The results of the implementation of aspects of students in cycle I obtained an average of 85.71% (B), and cycle II 96.42% (SB). d) The learning outcomes of students in cycle I obtained an average of 81.65 (B),and cycle II increased to 89.75 (B). Thus,it can be concluded that the Problem Based Learning (PBL) model assisted by Canva media can improve student learning outcomes in Pancasila education learning in class IV at SDN 21 Bandar Buat, Padang City.